5A.02: FITNESS STATUS AND RISK FOR ATRIAL FIBRILLATION. (June 2015) - Pittaras, A.; Faselis, C.; Doumas, M.; Manolis, A. J.; Grassos, H.; Kifnidis, K.; Kouremenos, N.; Papavasileiou, M.; Kallistratos, M.; Athanasiadis, I.; Kokkinos, P.
Abstract : Objective: Chronic, high-intensity physical activity has been associated with increased risk of developing atrial fibrillation (AF). Limited reports also suggest that even moderate levels of physical activity increase the risk for AF. Design and method: We performed a symptom-limited exercise tolerance test (ETT) in 6, 390 veterans (4, 401 blacks and 1, 989 whites), at the VAMCs in Washington, DC, between 1986 and 2012. All had no evidence of ischemia, AF or atrial flutter at the time or prior to ETT. We established four fitness categories based on age-stratified quartiles of peak metabolic equivalents (MET) achieved: Least-Fit category (4.9 ± 1.13 METs; n = 1, 578); Low-Fit (6.7 ± 1.0; n = 1, 613); Moderate-Fit (7.9 ± 1.0 METs; n = 1, 683) and High-Fit (9.3 ± 1.2 METs n = 1, 516). Multivariable Cox models were used to estimate hazard ratios and 95% confidence interval [CI] for AF across fitness categories. Results: During follow-up (median = 8.0 years), 838 developed AF. For every 1-MET increase in exercise capacity, the AF risk was 21% lower (hazard ratio, 0.79, 95% CI, 0.76–0.82, p < 0.001). AF risk was 23% lower for the Low-Fit (hazard ratio, 0.77; 95% CI, 0.65–0.91; p < 0.001); 46% for Moderate-Fit (hazard ratio, 0.54; 95% CI, 0.45–0.65; p < 0.001); and 64% (hazard ratio, 0.36; 95% CI, 0.29–0.45; p < 0.001) for High-Fit individuals. Conclusions: We observed an inverse, independent and graded association between exercise capacity and AF risk. The decline in risk was precipitous with only modest increases in exercise capacity. These findings support that increased fitness status achievable with moderate increases in physical activity as recommended by National and International guidelines lowers the risk for AF.